The Influence of Organizational Support and Turn of Duty on Performance Through Work Engagement in the Surabaya Transportation Department - Arifianti, Erny Lutfiyah; Fauzi, Akhmad; Swasti, Ika Korika (International Journal of Business and Applied Economics, 2024)
This research aims to examine the effect of organizational support and turn of duty on employee performance through work engagement at the Surabaya City Transportation Agency. This study uses a quantitative approach and survey technique involving Civil Servants at the Surabaya City Transportation Agency as respondents. Data was collected through questionnaires distributed to employees. Data analysis was performed using statistical techniques to test the relationships between the variables studied. The sample of this study consists of 76 staff-level employees from various work units and educational levels. The data from the sample were analyzed using Structural Equation Modelling (SEM) based on partial least squares (SEM-PLS). The findings indicate that: 1)  organizational support  has a non-significant effect on performance; 2) turn of duty  has a non-significant effect on performance; and 3)  organizational support has a significant effect on performance through work engagement; 4)  turn of duty has a significant effect on performance through work engagement. This indicates that although employee engagement at the workplace increases both through organizational support and turn of duty, it does not directly or indirectly enhance employee performance. Work engagement acts as a crucial mediator where employees who feel engaged with their work tend to have a better understanding of their duties and responsibilities and are intrinsically motivated to work responsibly.